Curriculum Management in Developing Learners’ Nobel Character at Pesantren - Wibowo, Andrian (IAIN Syekh Nurjati Cirebon, 2021)
The curriculum is one of the elements in the education system for determining the main activities in an educational institution. Pesantren is an educational institution, which created the learners to have a noble character and personality. That means, the curriculum in pesantren should be managed properly for presenting a superior education. This study aims to know how the planning, organizing, actuating, and evaluating of curriculum implementation in developing learners’ nobel character at pesantren Al-Ikhlash Kanggraksan. The methodology of this study is a descriptive case study with observation, interview, and documentation as data collection techniques. The data analysis of this study is data collection, data reduction, data presentation, and concluding. The result of this study is curriculum planning in developing learners’ nobel character at pesantren Al-Ikhlash Kanggraksan which includes activities of determining goals, determining the learning process, and determining learning materials. The learning management includes activities for managing learning materials, managing teachers, and managing time and schedules for teaching and learning activities. On the implementation, it educated learners to have good values in creating the character of the personality on their selves, such as ta'dzim, brotherhood, compassion, independence, and also exemplary through the methods of dirasah watta’lim, ta’dib, riyadhah and uswah hasanah. The evaluation of this implementation is the evaluation of test and non-test forms and indirectly it used the CIPP evaluation model (context, input, process, and product). Keywords: Curriculum, Pesantren, Nobel Character Kurikulum sebagai salah satu unsur pendidikan menjadi penentu utama kegiatan di dalamnya. Pesantren merupakan suatu lembaga pendidikan yang berorientasi membentuk santri yang berakhlakul karimah. Untuk mewujudkannya, maka pesantren perlu mengelola kurikulumnya dengan baik agar tetap menyuguhkan potret pendidikan yang unggul. Tujuan penelitian ini untuk mengetahui bagaimana perencanaan, pengelolaan, pelaksanaan serta evaluasi pelaksanaan kurikulum dalam mengembangkan akhlakul karimah santri di Pondok Pesantren Al-Ikhlash Kanggraksan. Metode penelitian yang digunakan ialah kualitatif deksiptif dengan pendekatan studi kasus melalui obervasi, wawancara dan dokumentasi. Teknik analisis datanya meliputi pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini ialah perencanaan kurikulum di pesantren Al-Ikhlash Kanggraksan meliputi kegiatan penentuan tujuan, penentuan proses dan materi pembelajaran. Pengelolaannya mencakup kegiatan pengelolaan materi pembelajaran, pengajar, dan waktu serta jadwal kegiatan belajar mengajar. Dalam pelaksanaannya mengajarkan nilai-nilai yang dapat mengembangkan akhlakul karimah santrinya seperti nilai ta’dzim, persaudaraan, kemandirian, dan juga keteladanan melalui metode dirasah watta’lim, ta’dib, riyadhah dan uswah hasanah. Evaluasi pelaksanannya menggunakan evaluasi bentuk tes dan non tes dengan model evaluasi CIPP (context, input, process, dan product).Kata Kunci: Kurikulum, Pondok Pesantren, Akhlakul Karimah